Star destroyers : big ships blowing things up - Daniel, Tony; Ruocchio, Christopher; Drake, David, 1945-; White, Steve, 1946-; Van Name, Mark L.; Kupari, Mike; Nye, Jody Lynn, 1957-; Dunn, J. R.; Williamson, Michael Z.; Rinehart, Gray; Lee, Sharon, 1952-; Bara, Dave (Baen, 2019)
Thus it was, and ever shall be, even into the distant future. From the oceans of Earth, to beneath the ice of Europa, to the distant reaches of galactic empires, it is the great warships and their crews that sometimes keep civilization safe for the rest of us, but sometimes become an extinction-level event in and of themselves.